Characteristics of Nanomaterials Based on Waste Paper with Variations in Heating Temperature and NaOH Concentration - Devi, Debby Sinta; Saloma, Saloma; Usman, Arie Putra; Saggaff, Anis; Ismail, Mohammad (Trends in Sciences, 2022)
Cementitious materials have been attempted to achieve more environmentally friendly construction materials. Nanomaterials with smaller particle sizes than cement can enhance the hydration gel structure. This report presents the processing of prepared waste paper into nanomaterials as raw materials available in abundant resources and supports the waste recycling process. Materials were processed by alkaline treatment using 5, 10 and 15 % NaOH solutions and 2 % NaClO at heating temperatures of 100, 125 and 150 °C. Testing the characteristics of the materials aims to determine the effect of heating temperature and concentration of NaOH used in the processing of nanomaterials. Based on the XRD test results, the use of lower temperatures showed that the amorphous phase, which is the main factor in the level of reactivity of the materials, tends to increase with increasing NaOH concentration. SEM morphology analysis showed that lower heating temperature was more effective in removing lignin content after alkaline treatment. The lignin content that can cause weathering needs to be removed and achieve maximum effect in bleaching nanomaterials based on waste paper. The particle size distribution results of nanomaterials were obtained with a size of 255-513 nm. Nanomaterials prepared from recycled materials are attracting interest as a new binder in nanocomposites. HIGHLIGHTS Nanomaterials with smaller particle sizes than cement can enhance the hydration gel structure The use of lower temperatures showed that the amorphous phase, which is the main factor in the level of reactivity of the materials, tends to increase with increasing NaOH concentration The lower heating temperature was more effective in removing lignin content after alkaline treatment Nanomaterials prepared from recycled materials are attracting interest as a new binder in nanocomposites GRAPHICAL ABSTRACT